In situ dissection of domain boundaries affect genome topology and gene transcription in Drosophila - Rodrigo G. Arzate-Mejía (Nature Portfolio, 2020)
In Drosophila, transcription is thought to be required for TAD formation, while the role of architectural proteins remains controversial. Here, the authors find that deletion of domain boundaries at the fly Notch locus results in TAD fusion and long-range topological defects, loss of architectural protein and RNA Pol II chromatin binding, and transcription defects.